Implementasi Media Pembelajaran Interaktif Budaya Indonesia Berbasis Android: (Studi : TK Jombor 1 Sukoharjo) - Apni Tri Gunarsih; Widiyanto Hadi; Muhammad Setiyawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research is a study aimed at developing media interactive study of Indonesian cultural materials based on androids, This interactive study media discussion is using interactive android-based androids.The research uses prototyping methods. The data analysis technique that the author used was a swot data analysis technique.Swot is to evaluate strength (strengths), Weaknesses, Opportunities and threats.To conclude the research on products made then there must be a test.The test used was the black box testing. The results of implementation are obtained from the interactive learning media of Indonesian cultural material based on Android, which consists of eight main menus namely: custom fashion, The custom house, Traditional weapons and local songs on students tk jombor 1 sukoharjo let the introduction of the Indonesian culture with user response very well proven by the index score of 90% respondents agree if this application is very helpful as an interactive media of Indonesian culture learning.